A case report of adult-onset COQ8B nephropathy presenting focal segmental glomerulosclerosis with granular swollen podocytes - Yujiro Maeoka; Toshiki Doi; Masaho Aizawa; Kisho Miyasako; Shuma Hirashio; Yukinari Masuda; Yoshihito Kishita; Yasushi Okazaki; Kei Murayama; Toshiyuki Imasawa; Shigeo Hara; Takao Masaki (BMC Nephrology, 2020)
Abstract Background Primary coenzyme Q10 (CoQ10) deficiency of genetic origin is one of a few treatable focal segmental glomerulosclerosis (FSGS). Renal morphologic evidence for COQ8B mutation and CoQ10 deficiencies of other gene mutations is assessed using electron microscopy with marked increase of abnormal-shaped mitochondria in podocytes. However, light microscopic morphologic features of deficiencies other than FSGS have not been reported. Case presentation A 30-year-old woman was admitted to our hospital because proteinuria was found during four consecutive medical checkups. She had no medical history or family history of proteinuria and severe renal dysfunction. The swollen podocytes were stained to the same extent as mitochondria-rich proximal tubular cells under both Masson’s trichrome and hematoxylin-eosin staining, whereas no mitochondrial abnormalities were detected under the first electron microscopic views. As proteinuria and estimated glomerular filtration rate (eGFR) deteriorated after pregnancy, we reevaluated the additional electron microscopic views and detected mitochondrial abnormalities. Genetic testing revealed COQ8B mutation (c.532C > T, p.R178W); therefore, we diagnosed COQ8B nephropathy. CoQ10 supplementation improved proteinuria and stopped eGFR reduction. Conclusions This is the first report of granular swollen podocytes due to mitochondrial diseases detected under light microscopy. We propose that this finding can be the clue for the diagnosis of both COQ8B nephropathy and the other CoQ10 deficiencies.